Tracy Letts’ August: Osage County as a Paradigm of Bad Parenting - Ghazi Mohammed, Marwa (International Journal of Language and Literary Studies, 2022)
One’s character is shaped by the family he/she has and the way he/she is raised up. Bad parents affect their children tragically, and the later consequences, the parents are the ones who pay for being bad ones. Tracy Letts explores the dark side of family life in his domestic play August: Osage County (2007), one of the most well-known contemporary plays of American theatre in the twenty-first century. The playwright presents the Westons as an embodiment of the image of family disconnected relationships due to bad parenting. Violet is a model of a bad mother who plays a prominent role in destroying her family. The impact of bad parenting is revealed in the circle of the formerly abused children who turned to be abusers of their children or the search for love and care in the others as an alternative to the parent image. This paper examines the reasons for being bad parents concerning Violet in particular and the psychological effects of her aggressive behavior and insufficient care for her three daughters. The importance of the study lies in demonstrating the shape of the characters of the daughters in facing the challenges of life.